Malady of lattice - Shobita Nair; Venugopal Anitha; Meenakshi Ravindran; Vinit J Shah (TNOA Journal of Ophthalmic Science and Research, 2021)
Lattice corneal dystrophy (LCD) is rare, bilateral, slowly progressive, inherited condition characterized by amyloid deposition in the corneal stroma. Recurrent corneal erosions most commonly occur with LCD due to abnormal basement membrane complexes incapable of providing normal structural integrity to the epithelial layer predisposing the cornea to microbial infections such as bacterial and fungal keratitis. Amyloid fibrils have also been postulated to cause tissue damage by stimulating local and nonlocal immune cell infiltration into the tissues and producing pro-inflammatory cytokines leading to sterile inflammation. This case is one of the few rare case reports of sterile infiltrates in LCD Type 1, patients identified after multiple treatment failures to the best of our knowledge.